RANDOM WRONGFUL CONVICTION AND EXONERATION, RARE COMPENSATION: A NEED FOR A COMPENSATION STATUTE IN BANGLADESH - Mohammad Saidul Islam (Universitas Negeri Semarang, 2019)
It is extremely difficult, not impossible, to determine the number of wrongful conviction in Bangladesh, mainly for the lack of initiative by the government and want of awareness among general people, advocates, rights groups, judges and others. It can undoubtedly be said that in Bangladesh many unjustly convicted are spending their lives in prison with intolerable sufferings and some of them have been released without any compensation. By analyzing the judicial decisions of the High Court Division of the Supreme Court of Bangladesh, the paper tries to highlight the frequency of wrongful conviction and exoneration in Bangladesh. This study also focuses the sufficiency of the present statute or tort law for compensating the unjustly convicted persons and highlights how better compensation can be ensured to the wrongfully convicted individuals in Bangladesh after consulting the statutes and States` practices of USA, UK, Canada, Australia, and India.